Moscas frugívoras (Tephritidae e Lonchaeidae): ocorrência, preferência de oviposição e tratamento hidrotérmico em frutos de tangerina (Citrus reticulata Blanco) do município de Matinhas, Paraíba - Lopes, Edson Batista (2007)
Matinhas municipality with approximately 1.3 million of tangerine tree (Citrus reticulata Blanco) ‘Dancy’ variety is responsible for 90% by tangerine production of the State of Paraíba. Frugivorous flies assumed economic importance in commercial tangerine groves because they cause premature dropping of fruits and significantly decrease of havest. The research was carried out in five geographic regions of Matinhas, municipality where twenty fruits on plant and twenty fruits under the plant had been collected, with the aim to search the occurrence of frugivorous flies and its levels of infestation in tangerine. Gotten results on occurrence showed that tangerine is infested by frugivorous flies Ceratitis capitata (Wiedmann, 1824), Neosilba zadolicha (McAlpine & Steyskal) and Neosilba glaberrima (Wiedmann, 1830). The infestation index mean of C. capitata in five regions did not exceed 0.5 pupae/fruit. The emergence percentage of (EP) of adults of C. capitata in fruits collected in plant and soil varied among 14.0 and 54.0% of adults/fruit. The gotten infestation index for N. zadolicha had variation among 0.4 and 4.3 pupaes/fruit. The data of emergence percentage (EP) of N. zadolicha had variation among 49.9 and 65.9% of adults/fruit, that specie being considered the most abundant and with high tax of survival. N.zadolicha specie was chosen as a primary and economic importance pest to tangerine fruit in Matinhas conditions. This is, also, the first report of these species N. zadolicha and N. glaberiima causing infestation in tangerine fruits in State of Paraíba.